Modified bisecting angle technique in eliminating zygomatic superimposition over apices of maxillary molars - Anshuman S Jamdade (Wolters Kluwer Medknow Publications, 2014)
Background: Image superimposition is a part and parcel of two-dimensional radiography. However, some overlappings are a result of radiographic technique itself. The technique induced superimposition of zygomatic buttress on apices of maxillary molars is common in bisecting angle technique (BAT), which affects the endodontic performance. Certain alterations were carried out in BAT to remove these undiagnostic shadows. The aim of this study was to compare two techniques of periapical radiography namely, BAT and modified BAT (MBAT) in preventing zygomatic superimposition over apices of maxillary molars. Materials and Methods: A total of 62 patients requiring endodontic treatment for at least one maxillary molar were recruited in this cross-sectional study. One tooth from every patient was subjected for two periapical radiographs, one with each BAT and MBAT respectively giving a total of 124 radiographs. Each radiograph was recorded as acceptable or unacceptable, based on zygomatic superimposition and different technical aspects. Chi-square test was used for data analysis. The kappa statistic was used to test intra-observer reliability. Results: With MBAT, the acceptability was 82.3% (n = 51) compared with 43.5% (n = 27) when BAT was employed. The statistically significant difference was found between these two techniques (P = 0.000). The level of agreement between two oral radiologists in their interpretation was high (kappa index = 0.897). Conclusion: Modified BAT was more accurate for periapical radiography of maxillary molars in preventing zygomatic superimposition and related technical errors than BAT.